Analysis of Asset and Financing Contribution to Islamic Banking Profit in Indonesia by Vector Autoregression (VAR) Method - Nofinawati; Dede Ruslan; Muhammad Fitri Rahmadana; Nasution, Adanan Murroh (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
The profit growth of Islamic banks in Indonesia tends to decline from the Covid-19 period to date. However, the number of assets and the amount of financing of Islamic banks tend to increase from one period to the next. This article discusses the contribution of assets and financing to the profitability of Islamic banking in Indonesia. This article was created using quantitative research methods. The data comes from the Financial Services Authority (OJK), namely data related to the amount of profit, assets, and financing in the Sharia Banking Statistics report, especially Sharia Commercial Banks from 2019 to 2023. Then the analysis of the contribution between the variables of assets, financing and profits of Islamic banks was analyzed using an econometric approach, namely the Vector Auto Regression (VAR) Method. The results of this study show that the profit variable of the previous period has a negative contribution to the endogenous profit variable. However, asset and financing variables in the previous period contributed positively to endogenous profit variables. There has been no previous research that discusses the contribution of variable assets and financing to the profit of Islamic banking in Indonesia using Vector Autoregressive Models. In order for the profit of Islamic banks to always increase, Islamic banks must always increase the number of their assets by increasing the amount of financing disbursed. Pertumbuhan laba bank syariah di Indonesia cenderung menurun dari periode Covid-19 hingga saat ini. Namun, jumlah aset dan jumlah pembiayaan bank syariah cenderung mengalami peningkatan dari satu periode ke periode berikutnya. Artikel ini membahas mengenai kontribusi aset dan pembiayaan terhadap profitabilitas perbankan syariah di Indonesia. Artikel ini dibuat dengan menggunakan metode penelitian kuantitatif. Data berasal dari Otoritas Jasa Keuangan (OJK), yaitu data terkait jumlah laba, aset, dan pembiayaan pada laporan Statistik Perbankan Syariah khususnya Bank Umum Syariah dari tahun 2019 sampai dengan tahun 2023. Kemudian analisis kontribusi antara variabel aset, pembiayaan dan laba bank syariah dianalisis dengan menggunakan pendekatan ekonometrika yaitu Metode Vector Auto Regression (VAR). Hasil temuan penelitian ini menunjukkan bahwa variabel laba periode sebelumnya memiliki kontribusi negatif terhadap variabel laba endogen. Namun, variabel aset dan pembiayaan periode sebelumnya berkontribusi positif terhadap variabel laba endogen. Belum ada penelitian sebelumnya yang membahas mengenai kontribusi variabel aset dan pembiayaan terhadap laba perbankan syariah di Indonesia dengan menggunakan Vector Autoregressive Models. Agar laba bank syariah selalu meningkat, maka bank syariah harus selalu meningkatkan jumlah asetnya dengan cara meningkatkan jumlah pembiayaan yang disalurkan.